2020
DOI: 10.1080/15022250.2020.1828163
|View full text |Cite
|
Sign up to set email alerts
|

Interactive value formation: drivers and outcomes from Airbnb guests’ perspectives

Abstract: This study explores interactive value formation, particularly the underlying drivers of three value outcomes in the Airbnb context: co-creation, co-destruction and co-recovery. The study focuses on reviews posted online by Airbnb guests in English. These posts contained customers' positive and negative experiences with Airbnb on Trustpilot. The data analysis uncovered two main themes that reflected the drivers of value co-creation, codestruction and co-recovery (company's customer service and hosts' actions). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 82 publications
2
20
1
Order By: Relevance
“…Some studies have indicated that a poorly maintained room has a negative impact on service quality attributes, such as facility condition (Ert et al , 2016) and the Airbnb accommodation experience (Sthapit et al , 2020). The accommodation provided by the host is considered a key service quality dimension of an Airbnb (Sthapit and Björk, 2020). The findings support studies indicating that the physical environment (Cheng and Jin, 2019) – is considered crucial for guests staying in Airbnb rental properties.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have indicated that a poorly maintained room has a negative impact on service quality attributes, such as facility condition (Ert et al , 2016) and the Airbnb accommodation experience (Sthapit et al , 2020). The accommodation provided by the host is considered a key service quality dimension of an Airbnb (Sthapit and Björk, 2020). The findings support studies indicating that the physical environment (Cheng and Jin, 2019) – is considered crucial for guests staying in Airbnb rental properties.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Airbnb allows property owners to gain additional income by renting out unused rooms, apartments and/or houses. Because of the dispersed ownership and management of Airbnb units, accommodation and experiences may vary widely (Sthapit and Björk, 2020). Airbnb can potentially expand supply wherever houses and apartment buildings already exist and individual hosts solely determine the prices of their Airbnb listings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper proposes a new model of memorable Airbnb experience, which was tested by examining the effect of the novelty of the experience, experience co-creation, hospitableness and facility service quality on memorable Airbnb experience. The study also examined the impact of such experiences on hedonic well-being, particularly in enhancing its the latter’s complexity and depth; previous studies have largely examined MTE and its conventional outcome variables, such as revisit intention (Sthapit and Björk, 2021; Zhang et al , 2018a, 2018b) and place attachment (Sthapit et al , 2019a, 2019b; Vada et al , 2019). In the context of this study, a memorable Airbnb experience refers to a positive Airbnb accommodation experience that is remembered and recalled in vivid detail thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to hotels, Airbnb accommodation can create a home-like experience, and thus is suited to provide a greater sense of wellbeing to travelers ( Suess et al, 2020 ). From the guest perspective, value can be destroyed by unethical actions of Airbnb hosts and poor communication that diminish guest wellbeing ( Sthapit and Jiménez-Barreto, 2019 ; Sthapit and Bjørk, 2021 ). Airbnb host–guest interactions can contribute to reducing loneliness for both groups thus enhancing their wellbeing ( Farmaki and Stergiou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%